Synthesis, structure–activity relationships and biological evaluation of dehydroandrographolide and andrographolide derivatives as novel anti-hepatitis B virus agents - Chen, Hao; Ma, Yun-Bao; Huang, Xiao-Yan; Geng, Chang-An; Zhao, Yong; Wang, Li-Jun; Guo, Rui-Hua; Liang, Wen-Juan; Zhang, Xue-Mei; Chen, Ji-Jun (Bioorganic & medicinal chemistry letters, 2014)
Dehydroandrographolide and andrographolide, two natural diterpenoids isolated from Andrographis paniculata possessed activity against HBV DNA replication with IC50 values of 22.58 and 54.07μM and low SI values of 8.7 and 3.7 in our random assay. Consequently, 48 derivatives of dehydroandrographolide and andrographolide were synthesized and evaluated for their anti-HBV properties to yield a series of active derivatives with lower cytotoxicity, including 14 derivatives against HBsAg secretion, 19 derivatives against HBeAg secretion and 38 derivatives against HBV DNA replication. Interestingly, compound 4e could inhibit not only HBsAg and HBeAg secretions but also HBV DNA replication with SI values of 20.3, 125.0 and 104.9. Furthermore, the most active compound 2c with SI value higher than 165.1 inhibiting HBV DNA replication was revealed with the optimal logP value of 1.78 and logD values. Structure–activity relationships (SARs) of the derivatives were disclosed for guiding the future research toward the discovery of new anti-HBV drugs. Dehydroandrographolide and andrographolide, two natural diterpenoids isolated from Andrographis paniculata possessed activity against HBV DNA replication with IC50 values of 22.58 and 54.07μM and low SI values of 8.7 and 3.7 in our random assay. Consequently, 48 derivatives of dehydroandrographolide and andrographolide were synthesized and evaluated for their anti-HBV properties to yield a series of active derivatives with lower cytotoxicity, including 14 derivatives against HBsAg secretion, 19 derivatives against HBeAg secretion and 38 derivatives against HBV DNA replication. Interestingly, compound 4e could inhibit not only HBsAg and HBeAg secretions but also HBV DNA replication with SI values of 20.3, 125.0 and 104.9. Furthermore, the most active compound 2c with SI value higher than 165.1 inhibiting HBV DNA replication was revealed with the optimal logP value of 1.78 and logD values. Structure–activity relationships (SARs) of the derivatives were disclosed for guiding the future research toward the discovery of new anti-HBV drugs.